Self‐Acupressure for Older Adults With Symptomatic Knee Osteoarthritis: A Randomized Controlled Trial. Issue 2 (29th December 2017) - Li, Lydia W.; Harris, Richard E.; Tsodikov, Alex; Struble, Laura; Murphy, Susan L.
Abstract : Objective: This double‐blind randomized controlled trial aimed to test the efficacy of self‐administered acupressure for pain and physical function improvement for older adults with knee osteoarthritis (OA). Methods: Participants were community‐dwelling adults with symptomatic knee OA (n = 150, mean age 73 years), randomized to 1 of 3 groups: verum acupressure, sham acupressure, or usual care. Participants in the verum and sham groups, but not those in the usual care group, were taught to self‐apply acupressure once daily, 5 days/week for 8 weeks. Assessments were collected during center visits at baseline, and at 4 and 8 weeks. In addition, pain level was assessed weekly by phone using a numeric rating scale (NRS). Outcomes included the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) pain subscale (primary), and subjective and objective physical function measures and the NRS and physical function measures (secondary). Linear mixed regression analysis was conducted to test between‐group differences in mean changes from baseline for the outcomes at 8 weeks. Results: Compared with usual care, both verum and sham acupressure participants experienced significant improvements in WOMAC pain (mean difference −1.27 units [95% confidence interval (95% CI) −1.95, −0.58] and −1.24 units [95% CI −1.92, −0.55], respectively), NRS pain (−0.74 units [95% CI −1.24, −0.24] and −0.51 units [95% CI −1.01, −0.01], respectively), and WOMAC function (−4.83 units [95% CI −6.99, −2.67] and −4.21 units [95% CI −6.37, −2.04], respectively) at 8 weeks. There were no significant differences between the verum and sham acupressure groups on any of the outcomes. Conclusion: Self‐administered acupressure is superior to usual care in pain and physical function improvement for older adults with knee OA. The reason for the benefits is unclear, and the placebo effect may play a role.